Emotional Intelligence in Saudi Arabian Educational Supervision: between acceptance and resistance - Jawaher Almudarra; David Menendez Alvarez Hevia (Educational Futures, 2019)
The concept of Emotional Intelligence has received considerable attention globally and most recently in the context of Educational Supervision in Saudi Arabia, where it has been presented as a key element to stimulate effective leadership and educational change. In this article, we discuss the introduction of Emotional Intelligence in Saudi Arabia, focusing on the experiences of six Saudi Educational Supervisors attending a workshop on Emotional Education. Qualitative data was generated from interviews, focus groups, participants observations and reflective diaries. Thematic analysis was used to organise the data and develop central ideas for discussion. Our interpretation of the data suggests that our participants have a limited understanding of the concept of Emotional Intelligence and that their views, which oscillate between acceptance and resistance, are influenced by Saudi culture as well as the model established by Daniel Goleman. In the final part of the paper provides some guidance on how to develop an alternative approach to Emotional Intelligence from a critical perspective.